Gender mainstreaming in Spain: policy instruments, influencing factors, and the role of local government. - Otero-Hermida, Paula; Lorenzo, Ramón Bouzas (Local Government Studies, 2020)
This article investigates equality policies in relation to gender mainstreaming in local governments, prior to the dismantling of equality policies in the wake of the financial crisis that began in 2008. Data from 198 municipalities based on the use of mainstreaming instruments revealed limited implementation of mainstreaming as a policy strategy. Similarly, a qualitative study on mainstreaming as a vision showed that the local level tended to reproduce supra-municipal deficits without offering a differential contribution. Lack of consistency was also observed between the role assigned to local entities by supra-municipal authorities and the role they actually played. Important influencing factors included the gender of the mayor, political colour of the local government, existence of a separate equality council, and adoption of an equality plan. The study concludes with recommendations for redefining local gender mainstreaming in a post-crisis scenario.